THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON STUDENT LEARNING OUTCOMES AT SMP NEGERI 20 REJANG LEBONG - Warniati Warniati; Fauzan Fauzan (International Journal of Teaching and Learning, 2025)
This study aims to determine the influence of the Problem Based Learning (PBL) learning model on the learning outcomes of junior high school students. This study uses an experimental method with a pre-test and post-test design on grade VIII students. The results showed that students who used the PBL model had higher learning outcomes compared to students who used the conventional learning model. The PBL model can improve student learning outcomes because students are given the opportunity to learn actively and independently. This research shows that the PBL model can be an effective alternative learning model to improve the learning outcomes of junior high school students. By using the PBL model, teachers can help students develop critical and creative thinking skills. This research is expected to be a reference for teachers and other researchers to develop more effective learning models.